Effects of the coastal salt gradient on the removal of the invasive clonal plants Carpobrotus sp. pl. (Aizoaceae) in a Mediterranean dune ecosystem - Maccioni, Alfredo; Dessena, Simone; Morittu, Samuele; Padedda, Bachisio Mario; Farris, Emmanuele (Frontiers in Conservation Science, 2025)
Invasive alien species represent an increasing threat to biodiversity conservation at both the species and ecosystem levels. Damages caused by invasive alien plants are more impactful when acting in areas of particular concentration of endemic species, such as biodiversity hotspots. In the Mediterranean Basin, one of the global biodiversity hotspots, the effects of alien plant invasions are well studied, especially in coastal environments. However, a lack of investigation on the effect of the coastal salt gradient on the interactions between native and alien plants seems to exist. Here, we explored the impact of the eradication of the invasive clonal plants referred to as Carpobrotus sp. pl. on vascular plant richness and diversity along a salinity coastal gradient in a dune system located in northern Sardinia (Italy). In the study area, we established three belts from the sea, each 50 m deep: at each belt, we eradicated Carpobrotus sp. pl. in 10 1 × 1 m plots; another 10 plots were controls with high coverage of Carpobrotus sp. pl., and another 10 plots were controls without Carpobrotus sp. pl. Since it was already demonstrated that soil salinity in dunes is negligible, we also measured sea aerosol salinity at each belt. We found that aerosol salinity was 0.0322 mg/cm2/day, corresponding to 1,174 kg/ha/year. In this paper, we show that belt was always a highly significant factor in all analyses we carried out, meaning that there were significant differences among the three belts for all the response variables investigated (bare soil and vegetation cover, number of species m−2, and Shannon index). This was especially true in those plots where Carpobrotus sp. pl. were eradicated. Our results show that the distance from the sea should always be considered when planning eradication actions, because the salinity gradient strongly influences the vegetation’s initial successional dynamics after the elimination of the alien plants.